Sources of Nominal Exchange Rate Fluctuations in South Africa - Gottschalk, Jan.; Bhundia, Ashok (Washington, D.C. : International Monetary Fund, 2003)
This paper investigates the sources of fluctuations in the rand-U.S. dollar exchange rate in 2001 and 2002 using an empirical exchange rate model which identifies aggregate supply, aggregate demand, and nominal disturbances as possible sources for exchange rate fluctuations. According to our results, nominal disturbances explain by far most of the rand depreciation in the final quarter of 2001. The fact that the nominal effective exchange rate also depreciated sharply suggests the nominal disturbances were domestically generated. From a preliminary examination of the relative movements in policy interest rates in South Africa and the United States, along with growth rates in both narrow and broad monetary aggregates in South Africa, it is difficult to isolate the underlying cause of the nominal disturbances in 2001 and 2002. Clearly, the task remains a challenging one with the empirical tools available.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet